Hydrodynamic design of multi-rotor tidal array - Cao, B (2020)
This thesis adopts a blade element actuator disc method, embedded in a Reynolds Average Navier-Stokes (RANS) solver, to design multi-rotor tidal arrays. The constructive interference effect is taken into account in the design process to maximize the hydrodynamic efficiency. The design process considers rotor arrays in a fence arrangement, investigating the relative merits of in-situ and uniform rotor designs. The designed rotor is fabricated and tested experimentally. The experimental results show that the rotor achieved superior power efficiency and substantial performance benefits are possible through the fence arrangement.